2020
DOI: 10.1039/d0nr00030b
|View full text |Cite
|
Sign up to set email alerts
|

A DFT screening of single transition atoms supported on MoS2 as highly efficient electrocatalysts for the nitrogen reduction reaction

Abstract: Re@MoS2 possesses the best NRR catalytic activity with a limiting potential of −0.43 V among TM@MoS2 systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 70 publications
2
87
0
Order By: Relevance
“…As shown in Figure 2a, for the MoS 2 system, the Mo atoms contribute to the valence band maximum (VBM) near the Fermi level (−0.03 eV), which also contribute to the conduction band minimum (CBM) about 1.65 eV. Therefore, the predicted bandgap of the MoS 2 monolayer is 1.68 eV, which is comparable to the literature [45,60] . Regarding the D‐MoS 2 system, the peak of Mo and S atoms are noticeably down‐shifted to 1.20 eV, and a new sharp peak appears above the Fermi level about 0.75 eV, which is primarily attributed to the formation of the vacancy defect.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…As shown in Figure 2a, for the MoS 2 system, the Mo atoms contribute to the valence band maximum (VBM) near the Fermi level (−0.03 eV), which also contribute to the conduction band minimum (CBM) about 1.65 eV. Therefore, the predicted bandgap of the MoS 2 monolayer is 1.68 eV, which is comparable to the literature [45,60] . Regarding the D‐MoS 2 system, the peak of Mo and S atoms are noticeably down‐shifted to 1.20 eV, and a new sharp peak appears above the Fermi level about 0.75 eV, which is primarily attributed to the formation of the vacancy defect.…”
Section: Resultssupporting
confidence: 72%
“…have predicted that the single Mo‐atom embedded MoS 2 nanosheets is an efficient NRR catalyst with an energy barrier of 0.53 eV [44] . Ge et al reported the excellent NRR performance of the single Re atom supported on MoS 2 [45] . Moreover, Zeng et al.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the DFT method is widely used for systems of TM atoms supported on 2D materials as SACs. Therefore, for calculational cost reasons and to facilitate comparisons with similar previous reports, [28][29][30][31] we adopted the DFT method in this study. Figure 9.…”
Section: Thermodynamic Stabilitymentioning
confidence: 99%
“…(e) Atomic models of single transition metal atom catalysts anchored on the B monovacancy of the h-BN monolayer [44] . [48] , Copyright © 2020, Royal Society of Chemistry Figure 5 (Color online) Catalytic performance of 2D MoS 2 for electroreduction of N 2 . (a) The optimized configurations (top and side views) of diatomic boron and single-atom boron doped MoS 2 nanosheets, as well as the main Mo-B bond lengths and binding energy [46] , Copyright © 2019, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…(b) Screening results of TM@MoS 2 systems for NRR processes using the free energy changes of two thermodynamically unfavorable protonation steps (ΔG(*N 2 -*NNH) and ΔG(*NH 2 -*NH 3 )) [47] , Copyright © 2017, John Wiley & Sons. (c), (d) Relationships between φ and ΔG(*NNH) and ΔG* [48] , Copyright © 2020, Royal Society of Chemistry [53] , Copyright © 2016, American Chemical Society. (b) NRR和HER的起始电位之差 [53] , Copyright © 2020, Royal Society of Chemistry.…”
mentioning
confidence: 99%